NATIONAL IDEA IN THE DISCOURSE OF THE UKRAINIAN SIXTY-EIGHTIES AS A CONSCIOUS CHOICE OF FREEDOM: FROM ACTION TO A NEW IDENTITY - Tarnashinska, Lyudmila (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The problem of national identity in the discourse of the Ukrainian sixties, in particular in the work and epistolary works of O. Zalyvakha, is examined. The thesis is developed according to which the representatives of this literary and artistic generation, having a calling for self-development, managed to make a choice in favor of personal and creative freedom under the conditions of a totalitarian regime, as a result of which they left a noticeable mark in the literature and art of the 20th century.Not only are the prerequisites for the development of the sixties resistance movement and its specificity of being between the imperative of a creative calling and a moral duty considered, but also the arguments regarding the national self-awareness of the passionate representatives of this generation as a kind of vertical: the conscious choice of freedom as a complex path from choosing a responsible act to acquiring a new identity.